Synthesis and Preliminary Anti-Inflammatory and Anti-Microbial Evaluation of New 4,5-Dihydro-1H-Pyrazole Derivatives - Shaymaa Kanaan K.; Tagreed N-A Omar (College of Pharmacy University of Baghdad, 2023)
Abstract      Organic compounds with pyrazole cores have a variety of uses, notably in the pharmaceutical and agrochemical sectors. The interest in creating pyrazole compounds, examining their many features, and looking for potential uses is growing. Our work has concert with synthesis of  chalcones and pyrazolines, then finally pyrazoline-aniline derivatives and evaluation their anti-inflammatory, antibacterial and antifungal activities